Interplay between psychosocial and heart failure related factors may partially explain limitations in self-efficacy in patients with heart failure: Insights from a real-world cohort of 1, 123 patients. (May 2022) - Calero-Molina, E.; Moliner, P.; Hidalgo, E.; Rosenfeld, L.; Verdú-Rotellar, J.M.; Verdú-Soriano, J.; Yun, S.; Garay, A.; Alcoberro, L.; Jiménez-Marrero, S.; Jose, N.; Calvo, E; et al.
Abstract: Background and aims: Worse self-care is associated with a higher risk of readmission and mortality in patients with heart failure (HF). Little is known about how the interplay between clinical and psycho-social factors may modulate self-care behaviours in these patients. The aim of our study was to identify clinical, and particularly psycho-social factors associated with worse self-care and assess their interaction inpatients with heart failure. Methods and results: We conducted an observational, prospective, cohort study of 1, 123 consecutive patients with chronic heart failure. Self-care was assessed with the modified European Heart Failure Self-care Behavior Scale 9-item version (EHFSCBS-9), and both clinical and psycho-social profile of the patients included were also meticulously evaluated. A total of 484 patients (43%) were women, mean age was 72 years, and mean left ventricular ejection fraction was 44.5%. In multivariable analyses combining clinical and psycho-social factors, low social support (OR 3.53, 95% CI [2.13-5.86]; p-value <0.001), absence of caregiver support (OR 2.16, 95% CI [1.34 -3.48]; p-value 0.001) and depressive symptoms (OR 2.40, 95% CI [1.53-3.77]; p-value <0.001) were independent determinants of impaired global self-care. Advanced functional class was associated with better self-care (OR 0.43, 95%CI [0.26-0.70]; p-value 0.001). No other clinical factors remained significantly associated with self-care in these joint models. In discrimination analyses, models containing psycho-social determinants outperformed models only containing heart failure -related (clinical) variables (all p-values<0.001). Conclusion: Impairment in self-care behaviour is strongly determined by psycho-social factors. Specifically, low social support, the lack of caregiver support and the presence of depressive symptoms are the main drivers of the risk of impairment of self-care in heart failure patients. Evaluation of self-care and self-care interventions should be complemented by a comprehensive psycho-social assessment in patients with heart failure. Abbreviations: DAMOCLES, Definition of the neuro-hormonal Activation, Myocardial function, genOmic expressionand CLinical outcomes in hEart failure patients; NYHA, New York Heart Failure Association; GAM, Generalized Additive Model; BMI, Body Mass Index; GDS, GeriatricDepression Scale.